SEJARAH DAN KARAKTERISTIK AL-QUR’AN DAN TERJEMAHNYA KEMENTERIAN AGAMA RI - Hamam Faizin (Lajnah Pentashihan Mushaf Al-Qur'an, 2021)
This article describes the history of the Al-Qur’an dan Terjemahnya (the Qur’an and its translation) of the Ministry of Religious Affairs since its first edition (1965) to the last edition (2019). The Al-Qur’an dan Terjemahnya have been revised for four times, namely in 1971, 1990, 2002 and 2019. The improvements were made at different times and by different teams, resulting in different characteristics in each edition. The Jamunu Edition (1965) was still seems very letterlijk (literal). Vernacular languages, especially that of Malay, are still widely used. The Saudi Arabia edition (1990) showed a luxurious packaging, yellow thin paper and a good cover. There are no substantial revisions. The 2002 edition underwent substantial changes in its translation, language style, reduction of footnotes, omission of introduction and paragraph subtitles. The 2019 edition also underwent changes in its substance of translation, language style, format, and systematic arrangement.